Percorsi nella Storia dell'arte Giornate di studi in onore di Maria Luisa Frongia (La biblioteca di Medea, 2021)
The volume contains the proceedings of the conference "Giornate di Studi in onore di Maria Luisa Frongia", held at the University of Cagliari on 6 and 8 June 2016. The essays look at a plurality of topics in a predominantly interdisciplinary perspective, embracing an arc chronological, geographical and historical-critical particularly wide. The horizon of studies is suggested and inspired by the interests of Maria Luisa Frongia, professor of History of Contemporary Art.